Care Management of Premarital Women Using Clear Counseling Techniques, Roles Body Attitudes and Gather Approaches - Siti Nur Endah Hendayani; Yeni Rosyeni; Tri Setiowati (Institute of Computer Science (IOCS), 2022)
Prevalence of child marriage in Indonesia has more than doubled in recent years but is still one of the highest in the East Asia and Pacific region crease of mother knowledge through education. This of course has an indirect impact on increasing high risk, both morbidity and mortality for mothers and babies to be born. Reproductive health of the bride and groom is a very important thing in order to prepare mothers to be the creators of a healthy and quality generation. The aims of this study is to conduct counseling management for premarital women with the CLEAR counseling technique, ROLES body attitude and the GATHER approach. This study uses a case study design with a descriptive observational method with a focus on the application of CLEAR, ROLES and GATHER counseling techniques. The subject of this case study is Ms. M, aged 24 years. This case study was carried out at PMB Siti Nuraeni in May 2022. Data was collected directly (primary data) using the Varney management approach and documentation in the form of SOAP (subjective data assessment, objective data assessment, data analysis and case management). Then the data were analyzed in descriptive analysis. Conclusion of this study that counseling technique used in premarital care cases is in accordance with the theory, namely by using the CLEAR technique (Clarifying, Listening, Encouraging, Asking for feedback, Repeating). Body posture uses the ROLES approach (Relaxing, Opening up the client, Learning toward the client, Establishing eye contact, Smiling and squarely). Implementation of counseling steps in premarital care cases is carried out according to the